Determinan Retensi Perawatan Berdasarkan Faktor Perilaku Klien Rehabilitasi Rawat Jalan - Djuningsih, Resky Fitriyanti; Poerwandari, Elizabeth Kristi; Harahap, Anggi Aulina (UI Scholars Hub, 2021)
The success of rehabilitation can be seen based on the length of treatment carried out by narcotics abusers. Institusi Penerima Wajib Lapor (IPWL) of the BNN DKI Jakarta area, as an outpatient rehabilitation service provider, has a fairly low treatment completion rate, namely 65% for male clients and 46% for female clients. The client's presence in rehabilitation is inseparable from the client's health behavior which is influenced by predisposing factors, enabling factors, and reinforcing factors. The existence of differences in the characteristics of drug abuse between men and women can also affect the behavior of clients. This study aims to analyze the factors that influence the behavior of clients in running an outpatient rehabilitation program. A mixed-methods approach was used in this study. The quantitative approach was carried out using a questionnaire with the method of factor analysis and multiple linear regression analysis of 79 clients who became the research sample. The qualitative approach was carried out using in-depth interviews with 9 informants consisting of clients and rehabilitation officers. The results showed that there was a significant influence between behavioral factors on client attendance. Of the 3 variables formed, family support has a significant influence on client attendance in outpatient rehabilitation services. In addition, regarding the differences in rehabilitation approaches between male and female clients, a rehabilitation program that is sensitive to women needs to be developed. The results of this study can be used by policy makers in improving the quality of outpatient rehabilitation services. Keywords: Treatment Retention, Behavior, Drug Abuser, Narcotics Rehabilitation, Outpatient